HUBUNGAN PENYAKIT PENYERTA (ANEMIA DAN DIABETES MELITUS), INFEKSI DAN ANTIBIOTIK DALAM PENYEMBUHAN LUKA POST OPERASI SECTIO CAESAREADI RUMAH SAKIT YADIKA KEBAYORAN LAMA TAHUN 2024 - farisma, Erni; Ginting, agus santi br.; sari, agustina (SINERGI : Jurnal Riset Ilmiah, 2025)
Post-sectio caesarea wounds are caesarean section scars that appear when a woman cannot give birth normally. The healing process consists of three phases: inflammation, proliferation (epithelialization), and maturation (remodeling). In the inflammatory phase, healing lasts until the fifth day after surgery and can be faster if there is no infection. This study aims to examine the relationship between comorbidities (anemia and diabetes mellitus), infection, and antibiotic use on post-cesarean wound healing at Yadika Hospital, Kebayoran Lama in 2024. The study used an analytical survey with a cross-sectional approach, and sampling was carried out by systematic random sampling of 30 mothers who gave birth through cesarean section. The results showed no significant relationship between anemia and post-cesarean wound healing with a P-value of 1.000, and no relationship between diabetes mellitus and wound healing with a P-value of 0.810. However, there was a significant relationship between infection and wound healing with a P-value of 0.000, and a relationship between antibiotic use and wound healing with a P-value of 0.000. In conclusion, there is no relationship between comorbidities (anemia and diabetes mellitus) and post-cesarean wound healing, but there is a relationship with infection and antibiotic use. Suggestions are given for mothers to improve their knowledge about the wound healing process after cesarean section surgery